2021
DOI: 10.30871/ji.v13i2.3460
|View full text |Cite
|
Sign up to set email alerts
|

Portable Solar Photovoltaic Suitcase

Abstract: This appliance is a micro-scale solar power plant intended for a temporary power source in areas affected by natural disasters in Indonesia that is portable, and is equipped with basic equipment such as a charger port and LED lights. The material used for the PV is aluminium with ceramic cooling which is designed in the form of a suitcase so that it is robust, water and fire resistant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Si can also increase the activity of antioxidant enzymes, which in turn can reverse oxidative stress and reduce the damaging effects of the element Boron on plants which can cause a decrease in photosynthetic activity, the amount of chlorophyll [12], and the activity of enzymes that activate CO2 assimilation [13]. Increased photosynthetic efficiency due to Si fertilization makes the absorption of nutrients by plants in the vegetative period more optimal and is able to increase growth determined by the parameter of plant height [14]. A number of studies have also reported that silica application can also induce plant resistance where when silica is absorbed by rice plants in large quantities, plant resistance to diseases and fungi will also increase [15].…”
Section: Plant Heightmentioning
confidence: 99%
“…Si can also increase the activity of antioxidant enzymes, which in turn can reverse oxidative stress and reduce the damaging effects of the element Boron on plants which can cause a decrease in photosynthetic activity, the amount of chlorophyll [12], and the activity of enzymes that activate CO2 assimilation [13]. Increased photosynthetic efficiency due to Si fertilization makes the absorption of nutrients by plants in the vegetative period more optimal and is able to increase growth determined by the parameter of plant height [14]. A number of studies have also reported that silica application can also induce plant resistance where when silica is absorbed by rice plants in large quantities, plant resistance to diseases and fungi will also increase [15].…”
Section: Plant Heightmentioning
confidence: 99%